DETERMINASI TINGKAT KEMISKINAN PROVINSI INDONESIA 2016-2020 - Tasya Putri Indra Pranizty; Yustirania Septiani (Universitas Teuku Umar, 2021)
The problem of poverty is a problem that is quite complex and every country has faced poverty, including Indonesia. The poverty level can be influenced by the TPT, dependency ratio, and education. The purpose of this research is to analyze how partially and simultaneously the influence of TPT, dependency ratio, and education (APS, APM, and APK in high school level) on provincial poverty levels in Indonesia 2016-2020. The data used is seconday data, in the form of time series (2016-2020) and cross section (34 provinces in Indonesia). The analytical tool used is panel regression analysis assisted by using Eviews 10. The results of this study indicate that the TPT has a positive and signigicant effect on the poverty level. The dependency ratio has a negative but insignificant effect on the poverty level. The education variable with the APS for high school education level has a positive and significant effect on the poverty level. The education variable with the proxy APM for high school education level has a positive and significant effect on the poverty level. And the education variable with the APK proxy for high school education level has a negative but insignificant effect on the poverty level. Simultaneously, open unemployment rate (TPT), dependency ratio, and education (APS, APM, and APK for high school education level) together influence the provincial poverty level in Indonesia in 2011-2020.